Antimicrobial efficacy of different toothpastes and mouthrinses: An in vitro study - Manupati Prasanth (Wolters Kluwer Medknow Publications, 2011)
Background: Anti-microbial agents have been used as a chemotherapeutic agent to improve oral health. This in vitro study was carried out to determine antimicrobial efficacy of different toothpastes and mouthrinses against the oral pathogens. Methods : A total of five toothpastes and five mouthrinses were tested for their antimicrobial activity against three oral pathogens namely, Streptococcus mutans (MTCC 890), Escherichia coli (MTCC 579) and Candida albicans (MTCC 854) by well agar diffusion assay. Statistical Analysis was performed using a statistical package, SPSS windows version 15, by applying mean values using analysis of variance (ANOVA) with post-hoc least square differences (LSD) method(α = 0.05). Results: Toothpaste formulation A showed maximum zones of inhibition against the test organism, Escherichia coli (P<0.001) compared to all other toothpastes formulations. Against Streptococcus mutans and Candida albicans, the zones of inhibition were less in comparison to E.coli but were significantly different at higher dilutions (1:8, 1:16 P<0.05) for toothpaste formulation A. Mouthrinses formulation H showed maximum efficacy against the test organism, Escherichia coli (P<0.001) compared to all other mouthrinse formulations. Against Streptococcus mutans, mouthrinses formulations F, G and J showed significant antimicrobial activity (P<0.05) compared to formulation H and I. Conclusion: In the present study, it has been demonstrated that triclosan containing toothpastes formulations are more effective in control of oral microflora compared to non-triclosan containing synthetic toothpastes. Among mouthrinses formulations, chlorhexidine was found to be more effective than or as effective as triclosan against the organisms tested.